1994
DOI: 10.1002/polb.1994.090320515
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic materials via ring‐opening polymerization of benzoxazines: Effect of molecular structure on mechanical and dynamic mechanical properties

Abstract: A series of benzoxazine compounds have been prepared from different bifunctional phenols and primary amines and the molecular compositions of the precursors are characterized by nuclear magnetic resonance, Fourier transform infrared, and size exclusion chromatography. It has been demonstrated that by design of the molecular structures of the benzoxazine precursors, therefore by tailoring of the network molecular architectures, new phenolic materials with superior mechanical and thermal properties, and ease‐of‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
285
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 296 publications
(294 citation statements)
references
References 1 publication
8
285
0
Order By: Relevance
“…The onset polymerization temperatures of Bra-1 and Bra-2 are 182 and 183°C, which are comparable to the polymerization temperatures of other benzoxazine monomers. [1][2][3] As it can be seen in Figure 5, Bra-1 and Bra-2 exhibited an exothermic peak centered at 228 and 232°C, respectively. As mentioned earlier, the polymerization temperatures of both Bra-1 and Bra-2 were 182 and 183°C, respectively.…”
Section: Thermally Polymerization Behavior Of Bra-1 and Bra-2mentioning
confidence: 92%
See 3 more Smart Citations
“…The onset polymerization temperatures of Bra-1 and Bra-2 are 182 and 183°C, which are comparable to the polymerization temperatures of other benzoxazine monomers. [1][2][3] As it can be seen in Figure 5, Bra-1 and Bra-2 exhibited an exothermic peak centered at 228 and 232°C, respectively. As mentioned earlier, the polymerization temperatures of both Bra-1 and Bra-2 were 182 and 183°C, respectively.…”
Section: Thermally Polymerization Behavior Of Bra-1 and Bra-2mentioning
confidence: 92%
“…It suggested that the ring opening reaction of benzoxazine had occurred in both Bra-1 and Bra-2 when the temperature increased to enough. [2,3] Figure 5 shows the DSC thermograms of Bra-1 and Bra-2 with the results summarized in Table 2. For Bra-1, there is a broad exotherm at around 125°C, which may be attributed to the reaction of double bond on the monomer.…”
Section: Thermally Polymerization Behavior Of Bra-1 and Bra-2mentioning
confidence: 99%
See 2 more Smart Citations
“…These benzoxazines were synthesized from monophenols, monoamines, and formaldehyde, but they could not form polymers with high molecular weight. After benzoxazines based on bisphenol-A were synthesized [5,6], a series of bifunctional benzoxazines have been prepared from bisphenols (or monophenols), monoamines (or diamines), and formaldehyde [7][8][9][10][11][12][13][14][15]. The bifunctional benzoxazines can form into polybenzoxazines with high molecular weight via thermally activated ring-opening polymerization reaction [16][17][18][19], and the resultant polybenzoxazines possess excellent properties, such as relatively high glass transition temperature, superior mechanical properties, excellent electrical insulation properties, low moisture absorption, high thermal stability, high char yields, and low flammability.…”
Section: Introductionmentioning
confidence: 99%